Analisis Faktor-Faktor yang Mempengaruhi Financial Distress pada Perusahaan Sektor Property, Real Estate, dan Building Construction di Indonesia - Miftahul Fauzy; Sri Astuti; Indra Kusumawardhani (Universitas Widyatama, 2019)
This study aims to determine and test the factors that influence financial distress. The factors in this study are liquidity, profitability, activity, and sales growth. Financial distress is measured using the Springate method. Liquidity is measured using the formula Current Ratio (CR), Return On Assets (ROA) is used to measure profitability, Total Asset Turnover (TAT) is used to measure activity and Sales Growth is measured by sales per year. The population in this study was 73 property, real estate, and building construction companies listed on the Indonesia Stock Exchange in the 2013-2017 period. Based on purposive sampling technique, 18 company samples were obtained that met the criteria for five years of observation with a total of 90 observational data. Data analysis techniques in this study used logistic regression analysis. The results showed that liquidity, profitability, and activities had a significant effect on financial distress, while sales growth had no effect on financial distress in property, real estate, and building construction companies listed on the Indonesia Stock Exchange in the 2013-2017 period.